On subgroups of saturated or totally bounded paratopological groups - Banakh, Taras; Ravsky, Sasha (Lugansk National Taras Shevchenko University, 2018)
A paratopological group \(G\) is saturated if the inverse \(U^{-1}\) of each non-empty set \(U\subset G\) has non-empty interior. It is shown that a [first-countable] paratopological group \(H\) is a closed subgroup of a saturated (totally bounded) [abelian] paratopological group if and only if \(H\) admits a continuous bijective homomorphism onto a (totally bounded) [abelian] topological group \(G\) [such that for each neighborhood \(U\subset H\) of the unit \(e\) there is a closed subset \(F\subset G\) with \(e\in h^{-1}(F)\subset U\)]. As an application we construct a paratopological group whose character exceeds its \(\pi\)-weight as well as the character of its group reflexion. Also we present several examples of (para)topological groups which are subgroups of totally bounded paratopological groups but fail to be subgroups of regular totally bounded paratopological groups.